Effect of growth temperature on glucosinolate profiles in Arabidopsis thaliana accessions. (October 2016) - Kissen, Ralph; Eberl, Franziska; Winge, Per; Uleberg, Eivind; Martinussen, Inger; Bones, Atle M.
Abstract: Glucosinolates are plant secondary metabolites with important roles in plant defence against pathogens and pests and are also known for their health benefits. Understanding how environmental factors affect the level and composition of glucosinolates is therefore of importance in the perspective of climate change. In this study we analysed glucosinolates in Arabidopsis thaliana accessions when grown at constant standard (21 °C), moderate (15 °C) and low (9 °C) temperatures during three generations. In most of the tested accessions moderate and pronounced chilling temperatures led to higher levels of glucosinolates, especially aliphatic glucosinolates. Which temperature yielded the highest glucosinolate levels was accession-dependent. Transcriptional profiling revealed also accession-specific gene responses, but only a limited correlation between changes in glucosinolate-related gene expression and glucosinolate levels. Different growth temperatures in one generation did not consistently affect glucosinolate composition in subsequent generations, hence a clear transgenerational effect of temperature on glucosinolates was not observed. Graphical abstract: The effect of different growth temperatures during subsequent generations on the secondary metabolites glucosinolates was investigated in different Arabidopsis thaliana accessions. Highlights: Growth temperatures of 21, 15 and 9 °C affect glucosinolates in Arabidopsis thaliana . Glucosinolate changes were quantitative and qualitative, and accession-dependent. Temperature preconditioning of parents did not affect glucosinolates in offspring.